Square‐ring metamaterial for radiation characteristics enhancement of an SIW cavity‐backed slot antenna. Issue 2 (30th September 2019) - Pandit, Soumen; Mohan, Akhilesh; Ray, Priyadip
Abstract: Design and analysis of a low‐impedance metamaterial (MTM) along with its application to antenna design are presented in this manuscript. This low‐impedance MTM is a square‐ring (SR) resonator, which exhibits low‐impedance property irrespective of the polarization and incident angle of the imposed EM wave. This SR MTM slab is placed directly atop an SIW cavity‐backed slot antenna for gain enhancement, eliminating the air gap between them. The peak realized gain improvement in the broadside direction is 8.3 dB, whereas the overall thickness of the antenna is 0.103 λ 0 at the operating frequency of 9.78 GHz. Moreover, the front‐to‐back ratio is 26.5 dB and the cross‐polarization is negligibly altered by this gain enhancement method. This concept is experimentally verified with fabrication and measurements.